Pengaruh Aksesibilitas Terhadap Karakteristik Sosial Ekonomi Masyarakat Pedesaan Kecamatan Bumijawa Kabupaten Tegal - Umrotul Farida (Jurnal Wilayah dan Lingkungan, 2013)
In Rural Areas, accessibility is one factor can stimulate the growth of markets and economic center. Like Bumijawa Subdistrict, as one of the rural areas in Tegal Regency is located in the mountainous area at the foot of Mount Slamet. Along with the development of transportation and road network, accessibility in some areas more easily. Community Activities also more develop, not only in agriculture, but also in other sector non-agriculture. Whereas in low accessibility areas, social economic community condition is still lagging behind due to difficult access to the area.  Accordingly, this study aims to determine how much accessibility effect to socioeconomic characteristics of rural community in Bumijawa Subdistrict, Tegal regency. The research approach used is a quantitative research approach. The method of analysis used in this study is descriptive Quantitative Analysis, crosstab analysis and spatial analysis. Based on the analysis result, found that the general conclusions are likely to affect the accessibility of community socio-economic conditions. Based on the result of socioeconomic zona, both in areas with high-level accessibility and area in around activities growth center are likely to have socio-economic conditions are more developed and conversely. When viewed from amount of influence on crosstab analysis, although it has a fairly strong correlation is between 0.309 to 0.702, but the magnitude of the influence of the level of accessibility to social conditions are still quite weak which only ranged from 0.049 to 0.254. This is because there are many other factors that also affect the socio-economic conditions of rural communities. In addition, one of them due to the low level of movement of rural communities compared with urban communities.